Feasibility of Group Telerehabilitation for Older Adults: A Quality Improvement Project - Emily M. Hudson; Stephanie P. Bazal; Michelle R. Rauzi; Hillari S. N. Olson; Melissa J. Ludescher; Christine Interrante; Molly Lahn; Estee Berg; Howard A. Fink; Jennifer P. Wisdom; Allison M. Gustavson (International Journal of Telerehabilitation)
A growing body of evidence suggests group rehabilitation may empower patients to achieve functional goals by leveraging social connectivity. From previous work, we adapted an in-person group for older Veterans to a telerehabilitation group called Fit for Life. The current quality improvement project aimed to evaluate the feasibility of implementing Fit for Life. Eligible Veterans lived in the community and were at risk for falls or hospitalization per functional performance measures. We used convergent parallel mixed methods approach in the evaluation. Eighteen Veterans ≥55 years old (all male, mean 77 years, 39% rural) received a referral to Fit for Life, two did not participate. We analyzed and integrated adaptations posed by clinicians and Veterans in real-time to enhance access to and participation in Fit for Life. Future work will explore clinical effectiveness, tools to identify patients most likely to benefit, and care delivery structures that integrate telerehabilitation groups for older Veterans.